Evaluation of sustainable and healthy eating behaviors and adherence to the planetary health diet index in Turkish adults: a cross-sectional study - Macit-Çelebi, Melahat Sedanur; Bozkurt, Osman; Kocaadam-Bozkurt, Betul; Köksal, Eda (Frontiers in Nutrition, 2023)
Aim The Planetary Health Diet Index (PHDI) is a relatively new index, and studies about its relationship with eating behaviors, nutritional status, and obesity in adults are very limited. For this reason, in this study, sustainable healthy eating behaviors of individuals and compliance of their diets with PHDI were evaluated. Methods This cross-sectional study was conducted with 1,112 adults (70.1% women and 29.9% men with mean age = 28.7 years, SE = 9.47). Study data were obtained with the face-to-face interview method via a questionnaire including sociodemographic characteristics, anthropometric measurements, the Sustainable and Healthy Eating (SHE) Behaviors Scale, and 24-h dietary recall. PHDI was evaluated for adherence to EAT-Lancet Commission recommendations. Results The average PHDI total score was 41.5 points. Higher SHE Behaviors Scale and PHDI scores were observed in participants with a duration of education above 8 years (p < 0.05). Those with lower SHE Behaviors Scale and PHDI scores were more likely to be obese (p < 0.001). The total PHDI score was positively associated with fiber, vitamin E, potassium, and folate, and negatively associated with pyridoxine and calcium (p < 0.05). The total SHE Behaviors Scale score was positively associated with carbohydrates, fiber, and potassium and negatively associated with pyridoxine, calcium, and energy (p < 0.05). A one-unit increase in SHE Behaviors Scale total score resulted in a 5,530 unit (95%CI: 4.652; 6.407) increase in PHDI total score and a one-unit increase in duration of education (years) resulted in a 0.660 unit (95%CI: 0.403; 0.918) increase in PHDI total score. Furthermore, a one-unit increase in Body Mass Index (BMI) (kg/m2) resulted in a − 0.218 unit (95%CI: −0.424; −0.013) decrease in PHDI total score. Conclusion The participants’ PHDI index scores were low; therefore, the adherence to the EAT-Lancet recommendation was low which might be associated with obesity. Clinical studies evaluating the effects of adherence to sustainable diets on adequate and balanced nutrition and health outcomes are recommended.